Women Leaders in the COVID-19 Crisis - Makasenan, I.V. (University of Jaffna, 2022)
Although the theory of feminism is gaining prominence in international politics, feminism in international politics remains a subject of constant debate. Demands for gender equality and struggles for women’s emancipation are a constant phenomenon. In the 2020s, the conversation about the impact of the outbreak of Covid-19, which plunged the world into a major crisis, is largely negative conversation. At the same time, the response of women political leaders to Covid-19 has elevated the discourse on women leadership in international politics and foregrounded feminist ideologies. Focusing on this, the main objective of this study is to identify the characteristics of women political leaders who take the lead in controlling the risks of the Covid-19 pandemic in their countries. The study is structured as a qualitative research methodology with descriptive analysis through secondary databased on this, the study explains that although the data indicates that the impact of Covid-19 has led to a breakdown in gender equality and that women have faced multiple oppressions, on the other hand it has indicated the superiority of women’s leadership. Many hope that responses to the crisis of female leadership will be a force for women’s recovery. Based on this, the impact of Covid-19 seeks to elucidate the importance of the role of women leaders in political power, which is widely believed to be male power.
Keywords: Covid-19; Feminism; Gender Equality; Political Dominance; Women Leadership